2016
DOI: 10.1021/acs.jced.6b00185
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbon Chain Length of Organic Salts on the Thermodynamic Stability of Methane Hydrate

Abstract: This study presents the phase equilibrium conditions for methane hydrate with one of the following organic ammonium salts differing in carbon chain length: tetramethylammonium bromide (TMAB), tetraethylammonium bromide (TEAB), tetrapropylammonium bromide (TPrAB), tetrabutylammonium bromide (TBAB), and tetrapentylammonium bromide (TPeAB). The hydrate phase equilibrium measurements were conducted for a temperature range of 278.94–291.85 K and pressure range of 4.79–14.32 MPa using the step-heating pressure searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 84 publications
5
12
0
Order By: Relevance
“…Phase equilibrium data on methane hydrate + (TEAB, TMAB, and TBAB) aqueous solutions with varying concentrations have also been used and compared from various literature. 5,10,11,20 The results on 0.05 mf of TMAB and TEAB obtained in this work are in good agreement with those obtained by Su and co-workers. 20 It has been observed from Figure 3 that TBAB shows significant hydrate promotion, while TMAB and TEAB show hydrate inhibition.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Phase equilibrium data on methane hydrate + (TEAB, TMAB, and TBAB) aqueous solutions with varying concentrations have also been used and compared from various literature. 5,10,11,20 The results on 0.05 mf of TMAB and TEAB obtained in this work are in good agreement with those obtained by Su and co-workers. 20 It has been observed from Figure 3 that TBAB shows significant hydrate promotion, while TMAB and TEAB show hydrate inhibition.…”
Section: Resultssupporting
confidence: 91%
“…Very few studies have been reported for methane hydrate formation in the presence of varying alkyl chain length of QASs in an aqueous solution. Recently, Su and co-workers 20 have investigated the phase equilibrium of methane hydrate + QASs aqueous solutions, such as TMAB, TEAB, TPrAB, TPeAB, and TBAB. TMAB, TEAB, and TPrAB were investigated at a single concentration (0.62 mol %), whereas TPeAB and TBAB were studied at two different concentrations (0.294 mol % and 0.62 mol %).…”
Section: Introductionmentioning
confidence: 99%
“…As for the effects on hydrate formation, gas solubility is just one factor. Su et al [87] and Gupta et al [88] observed that TBAB is a hydrate promoter, but TPAB, TEAB and TMAB are hydrate inhibitors.…”
Section: Salt Effectsmentioning
confidence: 99%
“…In evaluating the performance of QAS for gas hydrate inhibition, several methods has been applied, such as the T-cycle method and using highpressure micro differential scanning calorimetry equipment. The Isochoric constant cooling method or T-cycle method is one of the most used method, carried out by [37,[56][57][58][59][60][61][62] with different type of gases to study on the kinetic inhibition of the selected compounds. In this method, 100 mL of liquid sample is poured into the cell which is then vacuumed thoroughly to remove excess air that may still exist in the cell [20,63].…”
Section: Quaternary Ammonium Saltsmentioning
confidence: 99%